2021
DOI: 10.1021/acs.cgd.1c00625
|View full text |Cite
|
Sign up to set email alerts
|

Using HOESY NMR Spectroscopy to Characterize Prenucleation Aggregates

Abstract: Prenucleation aggregates are important species in the crystallization pathway. Here, we combine heteronuclear Overhauser effect spectroscopy (HOESY) and molecular dynamics calculations to study solute molecule association in a model systembenzoic acid/pentafluorobenzoic acid. Our findings indicate that HOEs arise from diffusion-limited prenucleation aggregates and that association is solvent dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Such a process has been recently proven by Bobrovs et al. who, while studying the prenucleation mechanism by means of HOESY NMR measurements, showed a high affinity of both co‐formers for the formation of binary systems [26] . Figure 9d depicts the 1 H‐ 19 F HOESY spectrum of a freshly prepared BA : PFBA/MCM‐41 sample.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Such a process has been recently proven by Bobrovs et al. who, while studying the prenucleation mechanism by means of HOESY NMR measurements, showed a high affinity of both co‐formers for the formation of binary systems [26] . Figure 9d depicts the 1 H‐ 19 F HOESY spectrum of a freshly prepared BA : PFBA/MCM‐41 sample.…”
Section: Resultsmentioning
confidence: 52%
“…Such a process has been recently proven by Bobrovs et al who, while studying the prenucleation mechanism by means of HOESY NMR measurements, showed a high affinity of both co-formers for the formation of binary systems. [26] Figure 9d depicts the 1 H- 19 F HOESY spectrum of a freshly prepared BA : PFBA/MCM-41 sample. The 2D NMR correlation takes 4 hours to acquire an appropriate number of serial files to achieve an acceptable resolution in an indirect dimension.…”
Section: Chemphyschemmentioning
confidence: 99%
“…Among the nuclei used in NMR, 1 H is the most important to study hydrogen-bond formation in solution. More sophisticated NMR techniques have also been extended to study co-crystal systems, e.g., Bobrovs et al have used heteronuclear Overhauser effect NMR spectroscopy (HOESY), to explore the interaction between benzoic acid and pentafluorobenzoic acid …”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of nucleation has been studied for over 100 years, yet our understanding of fundamental nucleation processes is still very limited. Nucleation plays an important role in a large number of processes across all areas of the natural sciences, for example, in the formation of bones and minerals in geology, in the preparation of protein crystals in structural biology, ,, but also across chemistry, , materials science, and nanoscience. , Unlike organic chemistry, where synthesis pathways of molecules can be designed based on the precise knowledge of the movement of individual electrons in the synthesis process, the synthesis of solid-state inorganic materials to a large extent relies on a combination of large parameter studies and trial-and-error experiments. ,, A greater understanding of nucleation of materials could facilitate the design of synthesis strategies of materials with much higher control. , As shown in 2008, Gebauer et al showed the formation of cluster species appearing prior to the nucleation of CaCO 3 . The discovery of these “prenucleation clusters” has in the past decade led to a large number of studies investigating the chemistry and interactions of the compounds and clusters formed before nucleation. ,,, However, the role of prenucleation species in the nucleation process is still not clear. It is thus still an open question if the nature of the prenucleaction species themselves has an impact on the formed material, or if they are necessary intermediates in the chemical reaction which we cannot control.…”
Section: Introductionmentioning
confidence: 99%